Laser/Electron Irradiation on Indium Phosphide (InP) Semiconductor: Promising Pathways to In Situ Formation of Indium Nanoparticles - Assis, Marcelo; Macedo, Nadia G.; Machado, Thales R.; Ferrer, Mateus M. [UNESP]; Gouveia, Amanda F.; Cordoncillo, Eloisa; Torres-Mendieta, Rafael; Beltrán-Mir, Hector; Mínguez-Vega, Gladys; Leite, Edson R.; Sambrano, Júlio R. [UNESP]; Andrés, Juan; et al. (Wiley, 2018)
In the current study, whether femtosecond laser and electron beam irradiation of indium phosphide (InP) are “green,” fast, and effective methods to produce metallic In nanoparticles is probed. High-resolution transmission electron microscopy and energy-dispersive X-ray spectroscopy are employed to investigate the formation and growth of In nanoparticles on InP. Density functional theory and quantum theory of atoms in molecules calculations are employed to reveal the nature of formation of In nanoparticles under electron beam irradiation. These results expand the fundamental understanding of the atomic processes underpinning the mechanism of In−P bond rupture during the transformation process induced by the electron irradiation of the InP crystal by increasing the total number of electrons in the bulk structure.
Keywords: electron beam irradiation; femtosecond laser irradiation; In; InP; metal nanoparticles